(untitled) (Nexo Revista Científica, 2018)
In view of the increasing oil interest shown by Spain and Morocco, the aim of this project is to test the risk of hypothetical spills of hydrocarbons in the eastern region of the Canary Islands waters and their surroundings through the Simulation Model of Hydrocarbon Transport (TESEO) and the Island Response and Operations System against Ocean Pollutants, in Spanish Sistemas Insulares de Respuesta y Operaciones Ante Contaminantes Oceánicos (SIROCO).